Construction of religious worldview among former female students of religious schools in Iran - Jafari, Fakhereh Khatibi (2013)
Passing more than three decades since the Islamic revolution, some scholars believe that Iran’s society, regardless of Iranian government’s Islamization project, is moving toward secularization particularly in micro, subjective, individual level. Some recent social researches conducted in relation to Iranians’ religiosity suggest that new forms of religiosity have been developing among Iranian people especially the new generation. To put simply, in this study, the researcher has attempted to explore the religious worldview construction of young former students of Islamic schools in Iran. Surprisingly, since today no study has been conducted concerning the religious beliefs and attitudes of young students of Islamic schools in Iran. Based on the research’s problem, the following research questions were posed: 1. What are the main types of religious worldview of former students of Islamic schools in Iran? 2. How has the religious worldview construction of former students of Islamic schools in Iran been influenced by parents and Islamic schools? A qualitative methodology was the research design employed in this study. Furthermore, this study is strongly influenced by phenomenology as a qualitative research method. In fact, data was collected mainly through interviews using a semi-structured question interview guide. In general, thirty young girls, 20 to 25 years old, who were former students of Islamic girl schools, were interviewed in this study. The interviewees were selected from young girls who have passed between four to twelve years (from age seven to eighteen) of study in Islamic schools and have graduated from the religious schools at least two years and at most five years before the time of the interviews. After analyzing the research’s data meticulously, four major religious worldview’ constructions have been made. The constructions were named respectively: The Moral Theism, The Religious Skepticism, The Experiential Islamism, and The Traditional Shiism. Briefly speaking, in this research, the religious worldviews of the young Iranian Muslim informants were demonstrated by considering several areas: firstly, the ideas and perceptions of the young Iranians regarding religion and religiosity, secondly, the general attitudes and feelings of the interviewees towards Islam and Shiism, and thirdly, their ideas and beliefs towards the pillars of Islam, the main principles and branches of Shi’a, and some basic Shi’a’s beliefs. In the broadest sense, findings of this study demonstrated that in spite of receiving long-term religious educations in family, educational environment and society, the religious worldview of research’s interviewees contains some central elements of secular worldviews. Regardless of various types of religious worldview investigated among young girls in this study, their religious worldview in general can be described as personal, individualized, selective and eclectic, undetermined and fluid, and emotion centered. In general, with some caution, it could be said that the subjectivities of the young Iranian girls who have been studied in this research in contrast with their objective world, are gradually moving towards secularization and de-sacralization processes. Put briefly, the finding of this research could help Iranian policy makers, parents and families, teachers and school’s principals, and religious authorities, to understand more profoundly the religious subjectivity of Iranian youths and also to comprehend their feelings and attitudes towards the Islamic beliefs and values.